On modelling and experimentation of planar grinding using abrasive pads with grits of defined geometries and distributions for enabling controlled surface texture - Zhou, Yuchen (2018)
The surface of diamond grinding tool manufactured by current production method exhibits stochastic nature in terms of different grit size, irregular geometry, random crystallinegraphic orientation, non-uniform spacing, and varying protrusion heights. These topography characteristics has been found having various negative effects for the abrasive performance, especially in high-precision applications, causing less controllable surface topography, inefficient chip flow, high working temperature and cutting force.